Stallion semen cryopreservation using different cryoprotective agents on the skim milk trehalosa extender - Arifiantini, R.I; Supriatna, I (Indonesian Animal Sciences Society, 2007)
Cryoprotective agents (CPAs), protect the sperm during cryopreservation. There are two general classes of CPAs, at first penetrating cryoprotectants, these pass through the sperm membrane and act both intracellular and extracellularly, and the second non-penetrating cryoprotectants, these act only extracellularly. The objective of this study was to evaluate the addition of different CPAs namely glycerol (G), combination of ethylene glycol with glycerol (EG) and dimethilformamide (DMF) using skim milk trehalosa extender. The semen collected from 3 stallions using artificial vagina twice aweeks. The semen was evaluated, centrifugated and diluted in skim milk extender supplemented with 50 mM trehalose and three different CPAs with the concentration of sperm were 200x106 ml-1. Extended semen was then packed into minitub 0.3 ml and equilibrated at 4oC for 2 hours, freeze in the liquid nitrogen vapor for 10 minutes and stored in liquid nitrogen container -196oC. After 24 hours, the semen was thawed at 37oC for 30 second. Results of this experiment indicated that the percentage of motile and viable sperm in skim trehalosa extender using DMF and glycerol better than combination of ethylene glycol and glycerol. Â Key Words: Cryopreservation, Stallion Sperm, Cryoprotectant